Cuantificación de la macrofauna en un vertisol bajo diferentes sistemas de manejo en el Valle del Cauca, Colombia - Marin, EP; Feijoo Martínez, Alexander; Pena, J. (2001)
Using the Tropical Soil Biology and Fertility (T. S. B. F.) methodology the biodiversity, the density and biomass of macrofauna was evaluated in a vertisol soil under four tillage systems and in a cocoa plantation with an undisturbed for more than 20 years. Soil under cocoa showed the highest values of biodiversity (47 u.t.), while mulch tiller treatment showed the highest density (122 ind. 0.062 m2) and direct seeding the highest value of biomass (5.44 g. 0.062 m2). Ants, Myriapoda and earthworms exhibited greater level of population density (41 ± 28; 15 ± 8 and 8 ± 5 ind. 0.062 m2, respectively) while the greatest contribution to biomass was made by earthworms and Coleoptera population with 2.3 ± 1.7 and 0.27 ± 0.32 g. 0.062 m2. Soil under cocoa plantation and direct seeding presented the highest proportion of macrofauna at the top 5 cm (58.2 and 51.1% respectively) while treatments with soil disturbance as mulch tiller, disk plowing and chisel plow the distribution of macrofauna was between 5 to 20 cm depth (55.8, 53.7 and 46.2%). This study evidenced the sensibility of the soils macrofauna to different tillage systems. Macrofauna quantifying could be used to evaluate soil conditions under different management methods.